Dielectric relaxation and trap-modulated DC breakdown of polypropylene blend insulation. (17th December 2019) - Li, Zhonglei; Zhong, Zhuoyan; Du, Boxue
Abstract: This work focuses on the dielectric relaxation of isotactic polypropylene (iPP), syndiotactic polypropylene (sPP) and atactic polypropylene (aPP) blended insulation. The relationship between dielectric relaxation and trap characteristics, as well as their effects on the breakdown properties of polypropylene insulation are investigated. Frequency domain spectroscopy (FDS) is employed to characterize the dielectric relaxation of PP blends at 50, 70 and 90 °C. Isothermal surface potential decay (ISPD) measurements are carried out to obtain the trap characteristics, and the dc breakdown strength is tested; thus, the mechanisms of trap characteristics on the dielectric relaxation and breakdown performance are analysed. The dielectric relaxation processes α and δ of PP blends can be attributed to segmental motions and carrier hopping, respectively. The α relaxation strength (Δ ε α) decreases with the addition of sPP, since the intermolecular interaction factor ( g) between PP molecules is weakened. The activation energy of δ relaxation is proportional to the shallow trap level, since the increased shallow trap level can pose higher potential barriers for carrier hopping. The higher crystallinity of PP blends can induce more deep traps in the boundaries of spherulites, and it can reduce the number of shallow traps that are mainly distributed in amorphous regions. The increased deep trap density serves a function to reduce the mean free path of charges and restrain impact ionization, resulting in an enhancement in the breakdown field. Graphical abstract: Image 1 Highlights: The α and δ dielectric relaxation processes of PP blends are attributed to segmental motions and carrier hopping. The α relaxation strength of PP blends decreases with the addition of sPP. The activation energy of δ relaxation is proportional to the shallow trap level of PP blends. The increased deep trap density reduce the mean free path of charges and results in an enhancement of breakdown field.